Modeling solution X-ray scattering of biomacromolecules using an explicit solvent model and the fast Fourier transform - Tong, Dudu (2015)
A novel computational method based on atomic form factors and the fast Fourier transform (FFT) is developed to compute small- and near-wide-angle X-ray scattering profiles of biomacromolecules from explicit solvent modeling. The method is validated by comparing the results with those from non-FFT approaches and experiments, and good agreement with experimental data is observed for both small and near-wide angles. In terms of computational efficiency, the FFT-based method is advantageous for protein solution systems of more than 3000 atoms. Furthermore, the computational cost remains nearly constant for a wide range of system sizes. The FFT-based approach can potentially handle much larger molecular systems compared with popular existing methods.